Hyperglycaemia attenuated C2C12 myoblast proliferation and induced skeletal muscle atrophy via modulating myogenic regulatory factors genes expression in diabetic rats - Chittipong Tipbunjong,; Wipapan Khimmaktong,; Chumpol Pholpramool,; Piyaporn Surinlert, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Diabetes mellitus is characterised by high blood glucose level termed hyperglycaemia (HG). It has been reported to affect skeletal muscle by inducing skeletal muscle atrophy and skeletal muscle protein degradation leading to impairment of muscle function. This study aimed to investigate the effects of HG on the expression of myogenic regulatory factor genes in muscle progenitor cells and in skeletal muscle. The number of C2C12 myoblasts cultured in HG condition was significantly decreased compared to control in dose and time dependent manner. In addition, the number of Ki-67 positive nuclei was significantly decreased after treatment under HG condition. Real time PCR showed significant suppression of MyoD and myogenin, while Myf5 gene expression was significantly enhanced, compared to control. Furthermore, histological examinations of muscle fibres showed atrophy of tibialis anterior (TA) muscle from diabetic rats. The frequency of distribution of muscle fibre cross-sectional area (MCA) in diabetic rats was shifted leftward from that of normal control rats. In contrast, the MyoD and myogenin expression in TA muscle of diabetic rats were significantly increased compared to normal control rats. This study provides novel knowledge on the changing myogenic regulatory factor gene expression in hyperglycaemic condition, both in vitro and in vivo, leading to skeletal muscle atrophy.